19.1: Exciton‐Adjustable Interlayers for Efficient and Lifetime Improved Warm White Organic Light‐Emitting Diodes Based on a Delayed Fluorescence Assistant Host. (28th November 2018) - Wang, Zhiheng; Li, Xiang-Long; Ma, Zerui; Cai, Xinyi; Cai, Chengsong; Su, Shi-Jian
Abstract : Recently, a new route to achieve 100% internal quantum efficiency white organic light‐emitting diodes (WOLEDs) was proposed by utilizing noble‐metal‐free thermally activated delayed fluorescence (TADF) emitters due to the radiative contributions by effective reverse intersystem crossing. However, a systematic understanding of their reliability and internal degradation mechanisms is still deficient. Here, we demonstrate high performance and operational stable purely organic fluorescent WOLEDs consisting of a TADF assistant host via a strategic exciton management by multi interlayers. By introducing such interlayers, carrier recombination zone could be controlled to suppress the generally unavoidable quenching of long‐range triplet excitons, successfully achieving remarkable external quantum efficiency of 15.1%, maximum power efficiency of 48.9 lm W −1 and LT50 lifetime towards 2000 h. Our findings also indicate that broadening the carrier recombination region as well as restraining exciplex quenching at carrier blocking interface make significant roles on reduced efficiency roll‐off and enhanced operational lifetime.